2008
DOI: 10.1007/s10164-008-0101-4
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive tactics and activity patterns of solitary carnivores: the Iriomote cat

Abstract: Felids are generally considered to be crepuscular and nocturnal in their activity, but few studies have attempted to analyze the variability of their activity patterns. We studied the daily activity of the Iriomote cat Prionailurus iriomotensis by radio-tracking on Iriomote Island, Japan. The general activity patterns of Iriomote cats showed slightly prevailing activity during dark periods of the day with particular peaks at dawn and dusk or during the early hours of the night. However, these patterns were cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 30 publications
2
21
1
2
Order By: Relevance
“…Our results were similar those from previous studies of leopard cats in other region (Thailand; Rabinowitz 1990, Grassman et al 2005, Iriomote island in Japan; Schmidt et al 2009), which reported that cat activity patterns were related with those of their prey. The main prey of the Tsushima leopard cat is small mammals (Inoue 1972, Tatara andDoi 1994), and two species of, murids (Apodemus speciosus and A. argenteus), their most important food items (Tatara and Doi 1994, Moteki unpublished), tend to be nocturnal (Nakata et al 2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results were similar those from previous studies of leopard cats in other region (Thailand; Rabinowitz 1990, Grassman et al 2005, Iriomote island in Japan; Schmidt et al 2009), which reported that cat activity patterns were related with those of their prey. The main prey of the Tsushima leopard cat is small mammals (Inoue 1972, Tatara andDoi 1994), and two species of, murids (Apodemus speciosus and A. argenteus), their most important food items (Tatara and Doi 1994, Moteki unpublished), tend to be nocturnal (Nakata et al 2009).…”
Section: Discussionsupporting
confidence: 92%
“…The main prey of the Tsushima leopard cat is small mammals (Inoue 1972, Tatara andDoi 1994), and two species of, murids (Apodemus speciosus and A. argenteus), their most important food items (Tatara and Doi 1994, Moteki unpublished), tend to be nocturnal (Nakata et al 2009). Schmidt et al (2009) reported that the activity of the Iriomote leopard cat seemed to be related with the period of peak activity of their main prey species: the evening peak of cat activity reflected peaks in vocal activity of several amphibians and the morning peak reflected a period of high activity of bird species. The activity patterns of the radio-collared cat in our study seemed to mirror those of the Tsushima leopard cat's main prey, small mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, I suggest that the Iriomote cat can endure on its small island despite a poor mammalian fauna by means of shifting principal prey items to seasonal migrators, particularly during winter. It is during this winter period, that the mating season of the cat takes place (Okamura et al, 2000); home range size and activity of male cats increase Schmidt et al, 2003Schmidt et al, , 2009). Thus, the food requirement of the cat should increase in that time.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the cats may shift their feeding tactics when switching their principal prey items. The movement pattern of the Iriomote cat varies in relation to seasons and local differences of habitats Sakaguchi, 1991;Schmidt et al, 2003Schmidt et al, , 2009. It may also vary in relation to shifting feeding patterns of the cat depending on seasonal difference of principal prey items.…”
Section: Discussionmentioning
confidence: 99%